ANALYSIS OF STUDENTS' DIVERGENT THINKING SKILLS IN TERMS OF EXTROVERT-INTROVERT PERSONALITY TYPE - Amelia, Iva Nur; Gunawan, Gunawan; Setyaningsih, Eka; Kusuma, Jaka Wijaya (Yayasan Education and Social Center, 2024)
This research aims to describe the divergent thinking skills of 8th-grade students of SMP Negeri 2 Purwokerto in terms of extrovert-introvert personality types. The research follows a qualitative descriptive approach, with a subject consisting of 29 students from class VIII at SMP Negeri 2 Purwokerto. The students were categorized into two groups, extroverts and introverts, with 3 students selected from each category using purposive sampling techniques. Data collection involved the use of questionnaires, tests, interviews, and documentation. The research data analysis technique encompassed data reduction, data presentation, and drawing conclusions.The research findings indicate that both extrovert and introvert personality types students written information to solve the given problems. However, in terms of fluency and flexibility aspects in question 1, extrovert students utilized a single problem-solving approach and provided one answer, whereas introvert students displayed the skills to present two problem-solving approaches and two answers. For question 2, both extrovert and introvert students demonstrated two answers and problem-solving methods. Introvert students were shown to require a conducive classroom atmosphere, while extrovert students were capable of adapting to varying classroom conditions